Delayed migration of soft tissue fillers in the periocular area masquerading as eyelid and orbital pathology. Issue 3 (18th March 2021) - Lin, Zhiheng; Dean, Andrew; Rene, Cornelius
Abstract : Soft tissue fillers used for facial rejuvenation can cause complications. We present two cases of late migration of injected fillers mimicking other pathology in the periocular area. Case 1 is a 52-year-old woman referred with chronic bilateral upper lid swelling, mimicking blepharochalasis syndrome, 5 1 /2 years after undergoing injection of hyaluronic acid filler in both brows. Extensive blood investigations were normal. Bilateral, sequential upper lid biopsy revealed migrated hyaluronic acid filler, which was successfully treated with hyaluronidase. Case 2 is a 62-year-old woman who presented with a right lower lid mass 8 years after undergoing injection of polyalkylimide gel into both cheeks. CT scanning confirmed an intermediate density soft tissue mass overlying the inferior orbital rim. Histology from surgical excision reported chronic granulomatous inflammation due to migrated polyalkylimide gel. An awareness of late migration of fillers causing eyelid swelling and masses in the periocular area will prevent unnecessary investigations and facilitate prompt management.